Čiščenje valjanega jekla s peskanjem - Legat, Franc (Kovine zlitine tehnologije, 1997)
Sandblasting machines for cleaning of steel in rods and coils, the productivity and characteristics of different processes, the nature and the shape of surface modifications as well as the characteristics of different steel sands are described and discussed on the base of industrial experience.
Keywords: jekla; peskanje; palice; žica; pesek; lastnosti